WALISONGO DAN VOICE OF BACEPROT: SYIAR ISLAM INKULTURATIF DI INDONESIA - Manggala, Jakobus Aditya Christie; Prakosa, Heru (Universitas Sanata Dharma, 2024)
Voice of Baceprot (VoB) is a heavy metal band consisting of three young Muslim sisters from Garut, Indonesia. The emergence of VoB is a catalyst in the Islamic world. In the context of the propagation of Islamic values, the presence of VoB with its heavy metal music can be compared to the propagation method applied by the Wali Songo to the Javanese community. Clifford Geertz gave the title to the Wali Songo as cultural brokers because of their role in synthesizing Javanese traditions with Islamic teachings. If Wali Songo used the macapat gamelan art traditions to spread Islam to the Javanese people, VoB chose the heavy metal music genre to spread Islamic values to the world today. VoB's choice of music with the heavy metal genre itself has certainly raised many questions, how Islam views music, especially heavy metal. The composition of VoB band personnel consisting of 3 young women with complete hijab clothing and singing heavy metal music as their stage identity not only makes VoB a cultural broker but also a political actor for Islamic women in the world arena. When analyzed with the framework of Christian theological reflection from theologian Kosuke Koyama, what VoB has done is part of the concept of contextual participatory theology. Koyama expresses the importance of respecting local culture and context in the appreciation and meaning of faith. Thus, VoB emerges as a unique and innovative representation in preaching, providing a new understanding of the role of women, and heavy metal music in today's Islamic world.AbstrakVoice of Baceprot (VoB) adalah sebuah band heavy metal yang beranggotakan tiga srikandi belia pemeluk Islam asal Garut Indonesia. Kemuncullan VoB merupakan katalisator dalam kancah dunia keislaman. Dalam konteks syiar nilai-nilai Islam, kehadiran VoB dengan pilihan musik heavy metalnya dapat disandingkan dengan metode syiar yang diterapkan oleh Wali Songo pada masyarakat Jawa. Clifford Geertz memberikan predikat kepada Wali Songo sebagai cultural broker oleh karena peran mereka yang mampu mensintesiskan tradisi Jawa dengan ajaran Islam. Apabila Wali Songo menggunakan tradisi kesenian macapat gamelan untuk syiar Islam kepada masyarakat Jawa, VoB memilih genre musik heavy metal untuk menyebarkan nilai Islam kepada dunia saat ini. Pilihan musik VoB dengan genre heavy metal itu sendiri tentunya telah menimbulkan banyak pertanyaan, bagaimana pandangan agama Islam mengenai budaya musik khususnya heavy metal, dan bagaimana itu dimaknai dalam kaitannya dengan keagamaan? Komposisi personil band VoB yang terdiri atas 3 perempuan belia dengan pakaian hijab lengkap dan menyanyikan musik heavy metal sebagai identitas panggung mereka tidak hanya menjadikan VoB sebagai cultural broker melainkan juga political actor bagi perempuan Muslim dalam kancah dunia. Apabila dianalisis dengan kerangka refleksi teologi Kristiani dari teolog Kosuke Koyama, apa yang telah dilakukan oleh VoB merupakan bagian dari konsep teologi partisipatoris kontekstual. Koyama mengungkapkan pentingnya penghargaan terhadap kebudayaan dan konteks setempat sebagai bagian integral dari penghayatan dan pemaknaan iman. Maka VoB muncul sebagai representasi yang unik dan inovatif dalam syiar, memberikan pemahaman baru tentang peran perempuan, dan musik heavy metal di dalam dunia Islam saat ini.